Blood groups and other polymorphisms in multiple sclerosis. Issue 1 (February 1976) - MacDonald, J. L.; Roberts, D. F.; Shaw, D. A.; Saunders, M.
Abstract : A comparative study was made of blood groups and other polymorphic systems in 136 patients with multiple sclerosis in the Newcastle area. The majority of systems showed no difference from normal frequencies, but differences in the ABO and rhesus systems are suggested.